La auditoria financiera y su incidencia en los estados financieros de la empresa Agripac del cantón Machala año 2020. - Rodriguez Vallejo, Maria Jose; Garcia Armijos, Sulay Micaela (Machala : Universidad Técnica de Machala, 2022)
The main objective of this work is to determine the incidence of the Financial Audit in the presentation of Financial Statements for the adequate decision making of the company AGRIPAC S.A of the city of Machala in 2020. The methodology implemented in the investigation has a focus qualitative-quantitative, through the review of documents and the inquiry to the personnel of the accounting area, sufficient audit evidence and competence will be prepared to determine the error made by not accounting for three sales of merchandise, this had an impact on the preparation and presentation of financial statements regarding the reasonableness of the balances. In the results of the investigation, the answers obtained from the survey applied in the company dedicated to the purchase and sale of candies were consolidated, where the information presented was analyzed and verified according to the methods and techniques applied in the investigative work entity. Getting to know how the administrative and accounting area of the company works through the application and use of International Auditing Standards and International Financial Reporting Standards for small and medium-sized companies, it was possible to detect which were the objects to studies where they were contributed. suggestions and recommendations to the owner of the company so that in this way the necessary corrective measures are taken to improve its shortcomings. The research project contains the contextual and conceptual framework of the investigation, the audit execution process, presentation of results, conclusions, recommendations, bibliography and annexes.
El presente trabajo tiene como objetivo principal ddeterminar la incidencia de la Auditoría Financiera en la presentación de Estados Financieros para la adecuada toma de decisiones de la empresa AGRIPAC S.A de la ciudad de Machala durante el año 2020. La metodología implementada en la investigación tiene un enfoque cualitativo-cuantitativo, mediante la revisión de documentos y la indagación al personal del área contable se logró obtener la evidencia de auditoría suficiente y competente para determinar el error cometido al no contabilizar tres ventas de mercadería, esto repercutió en la elaboración y presentación de los estados financieros en cuanto a la razonabilidad de los saldos. En los resultados de la investigación se consolidó las respuestas obtenidas de la encuesta aplicada en la empresa dedicada a la compra y venta de confites donde la información proporcionada fue analizada y comprobada de acuerdo a los métodos y técnicas aplicadas en ente trabajo investigativo. Logrando conocer como es el funcionamiento el área administrativa y contable de la empresa que mediante la aplicación y utilización de Normas Internacionales de Auditoría y las Normas Internacionales de Información Financiera para pequeñas y medianas empresas, permitió detectar hallazgos las cuales fueron objetas a estudios donde se aportaron sugerencias y recomendaciones al propietario de la empresa para que de esta manera se tome los correctivos necesarios para mejorar sus falencias. El proyecto investigativo contiene marco contextual, conceptual de la investigación, proceso de ejecución de la auditoria, presentación de resultados conclusiones, recomendaciones, bibliografía y anexos
Keywords: AUDITORIA FINANCIERA; CONTROL INTERNO; ESTADOS FINANCIEROS; HALLAZGOS